A Phenanthroimidazole‐based Fluorescent Turn‐Off Chemosensor for the Selective Detection of Cu2+ in Aqueous Media. (3rd July 2018) - Hwang, Suh Mi; Chae, Ju Byeong; Kim, Cheal
Abstract : A new phenanthroline‐based chemosensor 3‐(1H‐phenanthro[9, 10‐ d ]imidazol‐2‐yl)benzene‐1, 2‐diol (1 ) was synthesized for the recognition of Cu 2+ . Sensor1 showed selective fluorescence quenching for Cu 2+ in aqueous media. Detection limit (0.87 μM) for Cu 2+ was much lower than WHO guideline (31.5 μM). Sensing property of1 toward Cu 2+ was studied by fluorescence and UV–Vis titrations, and Job plot and ESI‐MS analyses. Moreover, turn‐off fluorescence mechanism of1 toward Cu 2+ induced by intramolecular charge‐transfer (ICT) and ligand‐to‐metal charge‐transfer (LMCT) was well demonstrated by theoretical calculations. Abstract :